Penentuan Hydroquinon menggunakan Metode The Reverse Phase-High Performance Liquid Chromatography (RP-HPLC) - R. K. Sanjaya; A. Restyana; N. Ismillayli; D. Hermanto (SAINS : Jurnal Kimia & Pendidikan Kimia, 2021)
The reverse phase high performance liquid chromatography (HPLC) method was used to determine the hydroquinone content. Determination was carried out under the optimum conditions of the RP-HPLC method including methanol as the mobile phase, flow rate 1 mL/min, running time 5 minutes, injection volume 20 L, UV detector, wavelength 290 nm with internal standard hydroquinone. The measurement results show that the reversed-phase HPLC method is a sensitive and high-precision method with a detection limit below 0.5% w/w. The results of determining the hydroquinone content in the preparation sample in the form of cream using the reverse phase HPLC method in sample A and sample B were 2.26% and 2.32%, respectively. Statistical analysis based on the RPD value of sample A and sample B has a value of less than 10%. Therefore, the reverse phase HPLC method is expected to be an accurate method for routine analysis of hydroquinone in cosmetic samples and pharmaceutical products.